2021
DOI: 10.1108/bij-03-2020-0095
|View full text |Cite
|
Sign up to set email alerts
|

Green product innovation and competitive advantage: an empirical study of chemical industrial plants in Jordanian qualified industrial zones

Abstract: PurposeGreen product innovation is a global industrial concern. This research examines the possible impact of green product innovation on firms' competitive advantage in industrial enterprises operating in qualified industrial zones (QIZs).Design/methodology/approachThis research follows a descriptive analytical methodology, testing two hypotheses formulated based on the reviewed literature among chemical industrial plants of the three Jordanian QIZs (Amman, Zarqa and Irbid) in Jordan. Following a preliminary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Pacheco et al (2018) established a role of green absorptive capacity in green innovation performance. Green innovation further improves the competitiveness (Al-Abdallah and Al-Salim, 2021). Zhang et al (2020) supported that green absorptive capacity improves favourable outcome of market based regulation linked to external knowledge adoption and delivers eco-friendly innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pacheco et al (2018) established a role of green absorptive capacity in green innovation performance. Green innovation further improves the competitiveness (Al-Abdallah and Al-Salim, 2021). Zhang et al (2020) supported that green absorptive capacity improves favourable outcome of market based regulation linked to external knowledge adoption and delivers eco-friendly innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Toward sustainability, many scholars stressed that green innovation is an excellent solution to help organizations gain two goals simultaneously, including ecological balance and economic profitability [3]. Besides, it can enhance the organization's position, brand value, and competitive advantage in the market [4,5]. Undoubtedly, research on the green innovation topic has witnessed a rapidly increasing trend in recent years [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the implementation struggles with various obstacles, which may impact the firms' efforts to reduce emissions and make green products. Moreover, Al-Abdallah and Al-Salim (2021) claimed that they must identify the barriers to green innovation implementation, aiming to help the enterprises to overcome them more easily [4]. The examples can be Gohoungodji et al, (2020) systematically reviewed previous studies and found that the automotive industry must overcome six major challenges [9].…”
Section: Introductionmentioning
confidence: 99%
“…Huang and Li, 2017) and its impact on both competitive advantages (e.g. Al-Abdallah and Al-Salim, 2021) and production processes (e.g. Awan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%